Internal Control And Fraud Prevention In Online Business In Indonesia - Arifia Yasmin; Anita Karunia; Harnum Hanifah (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
It is undeniable that online business in Indonesia has gone a rapid development, which is inseparable from internet technology development. Nonetheless, there is assurance internal controls that are effective and sufficient are applied in online businesses. Given the fraud problems in online business, internal control is certainly demanded. This paper aims to investigate information in online business and to determine the consequence of internal control of online business on fraud prevention and detection in Indonesia economy development, particularly online business. This research employed qualitative descriptive method using analysis, data as well as taking advantage of prevailing theories as underpinning information. Secondary data sources used are research journals and are based on the "Experian Global Fraud and Identity Report APAC published in 2019-2020”. The Experian Global Fraud and Identity Report APAC published in 2019 explains that 50% of businesses included in Indonesia suffered losses due to online fraud over the past 12 months. In 2020, Experian reported that 48% of Indonesian companies annually experienced an increase in fraud losses due to inability to recognize consumers.